Analisis Potensi dan Stakeholder Ekowisata Danau Lut Atas Kabupaten Bener Meriah Provinsi Aceh - Ihsan; Halus Satriawan; Rahmat Abbas (Journal Serambi Engineering, 2024)
Ecotourism is a travel industry that adopts environmentally friendly practices, protecting natural and cultural heritage. The research objective is to analyze the potential and stakeholders of Lut Atas lake ecotourism. Ecotourism potential using Natural Tourism Operations and Attractions Analysis (ODTWA) guidelines as well as stakeholder descriptions through the Stakeholder Grid. The results of the research show that ecotourism in the Upper Lut Lake area has tourist objects and attractions that are worth developing, although it has several obstacles and constraints. ODTWA that have the potential to be developed are natural panoramas, waterfalls, religious tourism, hot springs, mountain foot areas, orchid and edelweiss fields, agro tourism and natural beauty. Meanwhile for stakeholders were obtained in four categories, including the Key players, namely the Tourism Office, LPHK Waq Pondok Sayur and KPH III, Context Setters, namely Bappeda, Crowd namely Secretariat for Journalists and Subjects namely DLH and PKSM.